INCIDENCE OF ACCIDENTAL AWARENESS DURING GENERAL ANESTHESIA – A TERTIARY CANCER CARE HOSPITAL EXPERIENCE - Alam, Tanveer; Qureshi, Rabeea; Aziz, Maria; Khan, Asma (Journal of Postgraduate Medical Institute, 2022)
Objective: To find out the incidence of accidental awareness during general anesthesia in a cohort of cancer patients in a tertiary care center in Pakistan. Methodology: This was an observational study conducted on cancer patients undergoing surgery under general anesthesia in Shaukat Khanum Memorial Cancer Hospital and Reserach Center. A total of 1000 patients were interviewed by a registered nurse in the Post-Anesthesia Care Unit (PACU) using the modified Brice questionnaire. The outcome measured was the incidence of awareness and/or dreaming intra-operatively. Results: Among the total 1000 patients, 516 patients were male and 484 were females. There were 356 patients under the age of 40, 462 between the ages of 41 and 60, and 182 above 60 years. Most of the patients were American Society of Anesthesiologists (ASA) Grade 2 (n = 834), while 14 were ASA Grade 1 and 152 were ASA Grade 3. The total intravenous anesthetic was used on 83 patients, whereas balanced anesthesia was used on 917. Elective surgery was performed on 968 individuals, while emergency surgery was performed on 32 others. Two patients had definitive awareness (n = 2) and two patients described dreaming during surgery (n = 2). Conclusion: Our study found the incidence of awareness during general anesthesia in the adult cancer population to be at par, if not more than that reported worldwide.